Envelhecimento populacional e o surgimento de novas demandas de políticas públicas em Viana/ES - Oliveira, Anderson Silva (2015)
In the area of public policies more people are reaching older ages and living longer, increasing the demand for public services creating new necessities and requiring from the municipalities an efficient and wider service which allows to the elderly people favorable conditions to have a healthy and an active life. In order to provide a humble contribution that older people have an increasingly better quality of life was developed this research featuring aging in Viana a city with 7.8% of the elderly and identifying new public policy demands that arise linked to increased participation of older people in the total population. Conducting interviews with professionals from the city government the civil society representatives providing aid to elderly and finally the residents of more than 60 years helped to identify the main needs of the age group of 60 years or more. The greatest need according to those interviewed elderly include health care and leisure facilities. Further discussions conducting research and educational campaigns will help to end the still huge prejudice existing in Brazil that does not give the senior citizen their real value and significance.